Exploring antiemetic strategies in hematologic malignancies: a comprehensive literature review and evaluation of antiemetic efficacy in patients receiving high-dose chemotherapy prior to hematopoietic stem cell transplantation - Jordan, Karin; Jordan, Berit; Vanden Burgt, Jennifer; Jahn, Franziska (Supportive care in cancer, 2025)
Purpose: Most antiemetic studies have been conducted in patients with solid tumors receiving single-dose chemotherapy. A research gap leaves healthcare providers without clear guidance on effective antiemetic regimens and schedules for patients with hematologic malignancies undergoing high-dose multiday chemotherapy. This literature search identified antiemetic studies and assessed efficacy outcomes in the hematology setting, and specifically in patients receiving high-dose chemotherapy prior to hematopoietic stem cell transplantation (HSCT). - Methods: A literature review of both PubMed and Embase was performed for published studies evaluating antiemetic regimens including an NK1 receptor antagonist (RA) and/or a 5HT-3RA with/without dexamethasone in the hematology setting. Key features of all studies are reviewed, and antiemetic efficacy is summarized specifically for studies in which patients received high-dose chemotherapy prior to HSCT. - Results: Twenty-two of an initial 926 identified publications met the predefined inclusion criteria. The studies were heterogenous, with varying characteristics pertaining to randomization, control groups, size, cancer types, chemotherapies, antiemetics, and assessments, making cross-study comparisons and conclusions difficult. The range of response rates was wide with numerous studies showing complete response, no emesis or no nausea rates of less than 50%. Response rates were highest when an NK1 RA regimen was administered; however, an NK1 RA was underutilized and only administered in two-thirds of the studies. - Conclusion: The results reflect a significant clinical problem in preventing chemotherapy-induced nausea and vomiting (CINV) in patients with hematologic malignancies. The scarcity and heterogeneity of studies highlight challenges inherent in this area. This underscores a pressing need for rigorous randomized trials in hematology and HSCT assessing treatment-related CINV and effectiveness of antiemetic regimens.